Financial innovation in Islamic banks: evidence on the interaction between Shariah board and FinTech - Mohd Haridan, Nurfarahin; Sheikh Hassan, Ahmad Fahmi; Mohammed Shah, Sabarina; Mustafa, Hasri (Emerald, 2023)
Purpose This study aims to investigate the significant role of the Shariah Board (SB) in the innovation of digital finance products through SBs’ interaction with financial technology (FinTech).